Villains are destined to die. 3 - Suol, (Manhwa artist) (Ize Press, 2023)
"Life in hard mode for 'villain' Penelope Eckhart means with every step forward, she's shoved five steps back. Just as things were looking (relatively) better between her and the brothers, she finds herself coming to blows with Reynold, who insists on dredging up the past--an affront Penelope won't take lying down. To make matters worse, she ends up attending the hunting tournament hosted by the crown prince, and Callisto + weapons = a recipe for DANGER"--